2020
DOI: 10.1016/j.optlastec.2020.106498
|View full text |Cite
|
Sign up to set email alerts
|

Blue laser welding of multi-layered AISI 316L stainless steel micro-foils

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…An increased penetration into the arrester tab correlated with higher mechanical seam strength. DAS et al made similar observations for welding steel foils [39].…”
Section: Characteristics Of the Mechanical Strengthsmentioning
confidence: 61%
“…An increased penetration into the arrester tab correlated with higher mechanical seam strength. DAS et al made similar observations for welding steel foils [39].…”
Section: Characteristics Of the Mechanical Strengthsmentioning
confidence: 61%
“…Green laser beam sources are particularly advantageous for welding copper plates. Optimisation and finding the right parameters are still the basis of a considerable amount of research [8][9][10][11][12][13][14][15][16][17].…”
Section: State Of the Artmentioning
confidence: 99%
“…Given its very small spot beam size, BDL technology can also be applied extensively to thin foil manufacturing, such as in cutting and/or welding processes. Joining (welding) of thin foils has always been required, for example, in battery cell applications [3]. In addition, with a very small spot size, the heat distortion is also minimized, which means post-weld heat treatment to remove residual stresses may not be required [1].…”
Section: Introductionmentioning
confidence: 99%
“…Limited articles have been published on blue laser or blue diode lasers related to welding, cladding, and materials processing, and they are summarized in the following. Das et al [3] performed welding of multi-layered stainless steel (SS316L) by stacking 20 layers of micro-foils with a thickness of 0.025 mm onto a 0.2 mm thick SS316L foil sandwich and welded them together. They suggested that this welding technique is suitable for industrial needs, especially for electrical micro joining, as it results in free cracks, low porosity, and low spatter.…”
Section: Introductionmentioning
confidence: 99%